Are tropical storms a failure warning? Evidence from standardized school examinations. (September 2017) - Spencer, Nekeisha
Abstract: This paper examines the impact of tropical storms on student academic achievement. It uses hurricane destruction indexes which takes into account the physical characteristics of the storms relative to the location of each school along with standardized examination test scores to quantify the impact on student performance in Jamaica for the period 1994–2010. The results indicate that the average hurricane reduces students' test scores where the impact is significantly greater for larger storms. Although in the short term, estimates also suggest that tropical storms can have a non-negligible impact on returns to schooling.